Renewable Energy, A Tube Solar Collector using Nanofluids - Muhamad, Mat Noor (Faculty of Mechanical & Automotive Engineering Technology, 2022)
In both power generation and other energy sectors, renewable energy is gradually becoming an alternative to fossil fuels.